Embryonic Cerebellar Graft Morphology Differs in Two Mouse Models of Cerebellar Degeneration - Purkartová, Zdeňka; Tichánek, Filip; Kolinko, Yaroslav; Cendelin, Jan (Cerebellum, 2019)
Cerebellar diseases causing substantial cell loss often lead to severe functional deficits and restoration of cerebellar function is difficult. Neurotransplantation therapy could become a hopeful method, but there are still many limitations and unknown aspects. Studies in a variety of cerebellar mutant mice reflecting heterogeneity of human cerebellar degenerations show promising results as well as new problems and questions to be answered. The aim of this work was to compare the development of embryonic cerebellar grafts in adult B6CBA Lurcher and B6.BR pcd mutant mice and strain-matched healthy wild type mice. Performance in the rotarod test, graft survival, structure, and volume was examined 2 months after the transplantation or sham-operation. The grafts survived in most of the mice of all types. In both B6CBA and B6.BR wild type mice and in pcd mice, colonization of the host's cerebellum was a common finding, while in Lurcher mice, the grafts showed a low tendency to infiltrate the host's cerebellar tissue. There were no significant differences in graft volume between mutant and wild type mice. Nevertheless, B6CBA mice had smaller grafts than their B6.BR counterparts. The transplantation did not improve the performance in the rotarod test. The study showed marked differences in graft integration into the host's cerebellum in two types of cerebellar mutants, suggesting disease-specific factors influencing graft fate.
Keywords: Animals; nemoci mozečku; Neurodegenerative Diseases; Mice, Neurologic Mutants; Female; Brain Tissue Transplantation; transplantace mozkové tkáně; mozeček; ženské pohlaví; Mice; neurodegenerativní nemoci; myši; Cerebellar Diseases; Male; Mice, Inbred CBA; modely nemocí na zvířatech; transplantace fetální tkáně; Disease Models, Animal; Graft Survival; Cerebellum; Fetal Tissue Transplantation; zvířata; mužské pohlaví; myši inbrední CBA; Mice, Inbred C57BL; přežívání štěpu; myši inbrední C57BL; myši - mutanty neurologické